Parfit D. We Are Not Human Beings / trans. from Engl. U. V. Dobronravova - U. V. Dobronravova (Омский научный вестник: Серия "Общество. История. Современность")
The article presents a comparative analysis the views on the problem of personality identity by Neo-Lockeanism (Shoemaker, Parfit, Lewis) and Animalism (Olson, Snowden, Carter). A certain of main objections to the psychological criterion (the problem of too many thinkers, the too many persons problem, the thinking parts problem, etc.) are critically examined. Basic animalist intuitions are refuted by the embodied person view (McMahan)